Federal Worker Protection Standard emergency medical assistance - McDonald, S. K., author; Hofsteen, L. M., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet defines the emergency medical assistance requirements of the Worker Protection Standard (WPS).
Federal Worker Protection Standard
CEPEP 6/03, updated 6/06.
This fact sheet was revised as part of the Comprehensive Worker Protection Standard Awareness Project for Colorado.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Decontamination (from gases, chemicals, etc.) -- Government policy; Agricultural chemicals -- Physiological effect -- Colorado; Pesticide applicators (Persons) -- Health and hygiene; Pesticides -- Application -- Safety measures